Effectiveness of visits from community pharmacists for patients with heart failure: HeartMed randomised controlled trial. Issue 7603 (23rd April 2007) - Holland, Richard; Brooksby, Iain; Lenaghan, Elizabeth; Ashton, Kate; Hay, Laura; Smith, Richard; Shepstone, Lee; Lipp, Alistair; Daly, Clare; Howe, Amanda; Hall, Roger; Harvey, Ian
Abstract : Objective To test whether a drug review and symptom self management and lifestyle advice intervention by community pharmacists could reduce hospital admissions or mortality in heart failure patients. Design Randomised controlled trial. Setting Home based intervention in heart failure patients. Participants 293 patients diagnosed with heart failure were included (149 intervention, 144 control) after an emergency admission. Intervention Two home visits by one of 17 community pharmacists within two and eight weeks of discharge. Pharmacists reviewed drugs and gave symptom self management and lifestyle advice. Controls received usual care. Main outcome measures The primary outcome was total hospital readmissions at six months. Secondary outcomes included mortality and quality of life (Minnesota living with heart failure questionnaire and EQ-5D). Results Primary outcome data were available for 291 participants (99%). 136 (91%) intervention patients received one or two visits. 134 admissions occurred in the intervention group compared with 112 in the control group (rate ratio=1.15, 95% confidence interval 0.89 to 1.48; P=0.28, Poisson model). 30 intervention patients died compared with 24 controls (hazard ratio=1.18, 0.69 to 2.03; P=0.54). Although EQ-5D scores favoured the intervention group, Minnesota living with heart failure questionnaire scores favoured controls; neither difference was statistically significant. Conclusion This community pharmacist intervention did not lead to reductions in hospital admissions in contrast to those found in trials of specialist nurse led interventions in heart failure. Given that heart failure accounts for 5% of hospital admissions, these results present a problem for policy makers who are faced with a shortage of specialist provision and have hoped that skilled community pharmacists could produce the same benefits. Trial registration number ISRCTN59427925 .